Osobennosti special'noj podgotovki zenscin v sportivnom fechtovanii s ucetom faz biologiceskoj ceklicnosti - Ejder, E.; Bojcenko, S. D. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The problems concerning the influence of female biology on the flexibility of competitors during training and bouts was considered in the article. 160 elite fencers were examined to discover their biological cycle for the optimal planning of training for bouts. The expected growth in women's participation in sport and gymnastics during the last years described in the article also.